Representasi Nilai Moral dalam novel demi konten: Analisis Semiotika Roland Barthes terhadap tokoh Nola - Cahya, Intan Aulia (Maliki Interdisciplinary Journal, 2024)
The application of moral values ​​in every aspect of life is a very common priority. In an action or result of creation, such as a literary work in the form of a novel, moral values ​​remain a separate component for the writer in conveying messages, messages or reminders to readers. Novels present moral values, life and are not just imaginative narratives. The values ​​contained in the novel can be analyzed through dialogue, sentences and fragments of paragraphs with the aim of providing reflection material for readers. The method used in this research uses a qualitative descriptive method using Roland Barthes’ Semiotics theory with the source of research data being literary works in the form of novels. The data collection technique used is reading and note-taking. The results of the research show that the denotative meaning of moral values ​​in the character Nola is depicted as someone who adheres to normative values. As for the myths and moral values ​​of the character Nola, they are entirely the obligations of fellow human beings found in social and religious teachings